BiVO4/Rh–Ci/HCO3− hetero-/homogeneous dual co-catalyst-decorated photoanode system for photoelectrochemical water oxidation - Mehmood, Adeel; Chae, Sang Youn; Park, Eun Duck (Journal of Photochemistry and Photobiology A: Chemistry, 2023)
Bismuth vanadate is one of the most efficient photoanode materials for solar water-splitting. However, its performance is limited by two main factors: poor charge separation and slow water oxidation kinetics. Herein, Rh–Ci/HCO3− hetero-/homogenous dual co-catalysts were introduced on the BiVO4 surface to improve the water oxidation performance. This Rh–Ci/HCO3− dual co-catalyst system improved the water oxidation activity of BiVO4 by enhancing the charge injection efficiency and stabilizing the photoelectrochemical water oxidation kinetics. BiVO4 decorated with Rh–Ci/HCO3− exhibited a higher photocurrent (2.011 mA∙cm−2) at 1.23 VRHE than bare BiVO4 (1.217 mA∙cm−2).
Keywords: Bicarbonate; BiVO4; OER; Photoelectrochemical cell; Rhodium